1997
DOI: 10.1080/09629359791884
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of esculentoside A on prostaglandin E2 production from murine peritoneal macrophages and rabbit synovial cells in vitro

Abstract: Esculentoside A (EsA) is a saponin isolated from the roots of Phytolacca esculenta. Previous experiments have shown that it has strong antiinflammatory effects. To investigate the mechanism of anti-inflammatory effects of esculentoside A (EsA),[3H] arachidonic acid (AA) prelabelled murine macrophage and radioimmunoassay were used to test the effect of EsA on the total release of AA and prostaglandin E2 in culture supernatants. The results showed that EsA had no significant effect on the total release of AA fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, we focused on Esculentoside A (EsA, C 42 H 66 O 16 ), a saponin isolated from the root of Phytolacca esculenta , commonly known as a herb for the treatment of bacteria, viruses and inflammation, which is widely used in China [ 8 , 9 ]. Studies have shown that it has strong anti-inflammatory, anti-tumor, anti-viral, and immunomodulatory effects [ 8 , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we focused on Esculentoside A (EsA, C 42 H 66 O 16 ), a saponin isolated from the root of Phytolacca esculenta , commonly known as a herb for the treatment of bacteria, viruses and inflammation, which is widely used in China [ 8 , 9 ]. Studies have shown that it has strong anti-inflammatory, anti-tumor, anti-viral, and immunomodulatory effects [ 8 , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%